Self Control Remaja Broken Home untuk Berintraksi dengan Lingkungan Sosial - jamaludin As'ari; C. Casmini (Jurnal Hukum dan Demokrasi (JHD), 2023)
Self control carried out by broken home teenagers is a way to control peaking desires. Broken home families can influence children in interacting with their social environment. The purpose of this research is how broken home youth self-control to interact with the social environment. The method used in this study is qualitative and data collection by telephone and WhatsApp interviews. In this study there are 3 aspects that can describe the subject of a broken home, namely; 1) cognitive point of view: The form of a broken home; which includes the destruction of the household, finances, and loyalty. 2) affective point of view: The influence of parental divorce; which includes separation of residence, cut off communication, harsh words, hurt feelings, high emotional intensity, feeling comfortable with other people, estrangement with parents. and 3) conative point of view: Tendency to behave; which includes speaking in a high tone, and not maximal in self-control. The following is an analysis of the strategies used by broken home youth in controlling themselves by getting used to reading istighfar when the past overshadows them. Keywords: self control, broken home, social environment